Respuesta :

[tex]\huge\textsf{Hey there!}[/tex]

[tex]\mathsf{= (3^{-1}+4^{-1})^{-2}}\\\\\\\mathsf{3^{-1} = \bf {\dfrac{1}{3}}}\\\\\\\mathsf{4^{-1} = \bf \dfrac{1}{4}}\\\\\\\mathsf{= (\dfrac{1}{3}+\dfrac{1}{4})^{-2}}\\\\\\\mathsf{\dfrac{1}{3} + \dfrac{1}{4} = \bf \dfrac{7}{12}}\\\\\\\mathsf{= (\dfrac{7}{12})^{-2}}\\\\\large\text{Simplify above and you have your overall answer...}\\\\\\\boxed{\boxed{\large\textsf{Answer: }\mathsf{\bf \dfrac{144}{49}}}}\huge\checkmark[/tex]

[tex]\huge\textsf{Good luck on your assignment \& enjoy your day!}\\\\\\\\\frak{Amphitrite1040:)}[/tex]